Evaluation of the Cytotoxic Effect of Sorafenib on the HepG2 Cell Line in Different pH Environments - Gökmen, Sedat; Güvenç, Dilek (Etlik Veteriner Mikrobiyoloji Dergisi, 2025)
Hepatocellular carcinoma is the third-leading cause of cancer-related deaths. Sorafenib, an FDA-approved multiple kinase inhibitor, is used to treat advanced hepatocellular carcinoma. The microenvironment of cancer cells is acidic (pH 6.6–6.9) due to the Warburg effect. This acidic environment promotes cell survival, proliferation, invasiveness, metastasis, and chemotherapeutic resistance. Our aim was to identify the cytotoxic and antiproliferative effects of sorafenib on human hepatocellular carcinoma at different pH levels. HepG2 cell line was used as a human hepatocellular carcinoma, and different concentrations of sorafenib were applied to HepG2 for 24 hours in media with pH values of 6.6, 6.8, 7.2, 7.6, and 7.8, respectively. The cytotoxic effects of sorafenib were determined with the WST-8 assay. Proliferation was evaluated using live-cell analysis and an imaging system. Sorafenib’s inhibitor concentration 50 value was 13.40 μM. Sorafenib showed the strongest cytotoxic effect on HepG2 cells at pH 7.6 (p<0.05). According to the proliferation test, sorafenib prepared at pH 7.6 induced a significant decrease (15.84±0.53, p<0.001) in proliferation when compared to the control and sorafenib prepared at pH 7.2 and 6.6. This study showed that an alkaline microenvironment increases the cytotoxic and antiproliferative effects of sorafenib.